Impact of SQ3R-assisted digital media on reading comprehension skills - Fauziah Ratu Dewi Kirana; Septi Fitri Meilana (Curricula: Journal of Curriculum Development, 2025)
Reading comprehension is a crucial skill in elementary education, serving as the foundation for understanding written information across subjects. However, many students still face difficulties in deeply understanding texts. This study aims to investigate the effect of the SQ3R (Survey, Question, Read, Recite, Review) method assisted by digital media on students’ reading comprehension skills. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. The sample consisted of two classes: the experimental group was taught using the SQ3R method integrated with digital video media, while the control group received conventional instruction. Data were obtained through pretests and posttests and analyzed using t-tests. The results revealed a significant difference between the posttest scores of the experimental and control groups, with a significance value of < 0.001. Additionally, the effect size (Cohen’s d = 2.323) indicated a very strong effect. These findings suggest that the SQ3R method, when combined with digital media, can significantly improve students’ reading comprehension. The integration of structured reading strategies with engaging multimedia support offers a promising solution for enhancing learning outcomes and supporting literacy development at the primary level.   Abstrak Pemahaman membaca merupakan keterampilan yang sangat penting dalam pendidikan dasar, berfungsi sebagai landasan untuk memahami informasi tertulis di berbagai mata pelajaran. Namun, banyak peserta didik masih mengalami kesulitan dalam memahami teks secara mendalam. Penelitian ini bertujuan untuk menyelidiki pengaruh metode SQ3R (Survey, Question, Read, Recite, Review) yang didukung oleh media digital terhadap keterampilan pemahaman membaca peserta didik. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi-eksperimental menggunakan kelompok kontrol yang tidak setara. Sampel terdiri dari dua kelas: kelompok eksperimen diajarkan menggunakan metode SQ3R yang diintegrasikan dengan media video digital, sementara kelompok kontrol menerima pengajaran konvensional. Data diperoleh melalui pretest dan posttest dan dianalisis menggunakan uji t. Hasil menunjukkan perbedaan yang signifikan antara skor posttest kelompok eksperimen dan kontrol, dengan nilai signifikansi < 0.001. Selain itu, ukuran efek (Cohen’s d = 2.323) menunjukkan efek yang sangat kuat. Temuan ini menyarankan bahwa metode SQ3R, ketika diintegrasikan dengan media digital, dapat secara signifikan meningkatkan pemahaman membaca peserta didik. Integrasi strategi membaca terstruktur dengan dukungan multimedia yang menarik menawarkan solusi yang menjanjikan untuk meningkatkan hasil belajar dan mendukung pengembangan literasi di tingkat sekolah dasar. Kata Kunci: kemampuan membaca pemahaman; media digital; metode SQ3R